VACCINATION FOR ADOLESCENTS IN THE EUROPEAN REGION: CURRENT STATE OF THE PROBLEM - Leyla S. Namazova-Baranova; Daria S. Chemakina; Marina V. Fedoseenko; Elena A. Vishneva; Lilia R. Selimzianova; Ksenia M. Gayvoronskaya (Педиатрическая фармакология, 2017)
This article describes the peculiarities of the National immunization programs for adolescents in the WHO Euro region. A comparative analysis of the groups was conducted based on economic development. The best and the worst performing states were identified in every group. It was demonstrated that economic development is not the leading factor that determines a country’s vaccination policy.